Kajıan Hukum Terhadap Korban Pemerkosaan: Perspektıf Hukum dı Indonesıa - Rinto Sibarani; Abdurrakhman Alhakim (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Rape is a crime that cannot be forgiven, because it causes mental and psychological damage to the victim and robs the future of the victim, for this reason there is a need for legal protection given to rape victims and rape victims who perform abortions. The form of protection can be in the form of restitution, compensation and psychological assistance given to the victim and also the protection provided by the health law related to the rules that allow rape victims to perform abortions on the baby they are carrying. This article uses a normative juridical research method with a statutory approach which is certainly very relevant to the theme that will be studied. Therefore, it is necessary to protect the victims of rape in order to exercise human rights against the victims and to give appropriate punishments to the perpetrators